The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/dme.14404
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of persons with diabetic and non‐diabetic neuro‐osteoarthropathy after foot correction using external fixation

Abstract: Aim Diabetic neuro‐osteoarthropathy (Charcot foot) is a serious form of diabetic foot syndrome, often leading to severe deformity of the foot and subsequently to ulcers and osteomyelitis. The aim of this retrospective study was to determine the success rate and long‐term outcomes for a Charcot foot operation using external fixation in 115 individuals who underwent surgery between July 2008 and December 2012. Methods Some 115 consecutive persons, 78 (68%) men and 37 (32%) women, were enrolled in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…In comparison to surgical literature, we could find similar rates in limb salvage (92.9%) compared to studies with similar length of follow-up: 93.7% limbs could be saved according to Fragomen’s series of 16 reconstructed feet[ 40 ]. Another recent study by Spraul et al reported a limb salvage rate of 89% while using the Hoffmann-external Fixator[ 41 ]. In a recent study with a mean of 35 months follow-up that analyzed the outcome of a one-staged reconstruction procedure using the Ilizarov principles, Wirth et al reported successful limb salvage in 93% [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to surgical literature, we could find similar rates in limb salvage (92.9%) compared to studies with similar length of follow-up: 93.7% limbs could be saved according to Fragomen’s series of 16 reconstructed feet[ 40 ]. Another recent study by Spraul et al reported a limb salvage rate of 89% while using the Hoffmann-external Fixator[ 41 ]. In a recent study with a mean of 35 months follow-up that analyzed the outcome of a one-staged reconstruction procedure using the Ilizarov principles, Wirth et al reported successful limb salvage in 93% [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wichtige neue Daten zu den Ergebnissen nach Behandlung der diabetischen Neuroosteoarthropathie (sog. Charcot-Fuß) kommen von der Arbeitsgruppe des Referenten selbst zusammen mit der chirurgischen Gruppe von Dr. Koller [ 23 ]. Dabei wurden 115 Patienten mit und ohne Diabetes nachuntersucht, bei denen in einem Zentrum konsekutiv zwischen 2008 und 2012 eine rekonstruktive Stellungskorrektur unter Verwendung eines Hoffmann-II-Fixateur externe durchgeführt worden war.…”
Section: Diabetisches Fußsyndromunclassified
“…Once established, deformity following a Charcot process can require surgical intervention to minimise risk and to restore a functional foot. In this issue, data following external fixation of the reconstructed Charcot foot are presented 6 . The surgical results are impressive with mobility restored postoperatively in almost all participants and maintained in most.…”
mentioning
confidence: 99%